The Importance of Governments' Response to Natural Disasters to Reduce Terrorist Risk. (19th September 2021) - Fisher, Daren; Dugan, Laura
Abstract: The increased incidence of natural disasters may be among the major forces driving crime over the coming century. Indeed, previous research suggests that natural disasters provide the catalyst for acts of terrorism. However, because governments can choose how they respond to natural disasters, they might be able to select actions that would mitigate hostile reactions. In this article, we argue that government responses' natural disasters could alter the rational motivations for terrorism. If true, then by responding adequately to a disaster, a government can also reduce both political violence risks and public health harms. This study argues that it is the portrayal of government responses to a natural disaster that impacts subsequent terrorism rather than the natural disaster itself. Using data from the Philippines, Turkey, and the United Kingdom between 1987 and 2013, findings suggest that when disasters occur, governments have a unique opportunity to diminish the incentives for terrorism.